Preadolescent exposure to a sexually mature, unrelated male rat reduces postadolescent social recognition memory and CA2 c-Fos labeling - Maletta, Teresa; Palummieri, Michael; Correa, Jeff; Holahan, Matthew R. (Frontiers in Behavioral Neuroscience, 2023)
Social memory involves social recognition: the ability to discriminate between two or more conspecifics when one has been previously encountered. The CA2 region of the hippocampus has been implicated in social memory, as lesions and dysfunction to this area lead to social memory impairments. A variety of psychogenic manipulations during postnatal sensitive developmental periods are associated with social memory impairments later in life. In this study, we exposed preadolescent rats to a sexually, mature unrelated male and examined whether this was associated with changes in postadolescent social memory and c-Fos labeling in the CA2 region. Male and female Long-Evans rats were exposed to a male, adult rat on postnatal days 19 – 21 (P19-21). Social memory was measured during the postadolescent period and defined as increased interactions towards a novel age-matched rat in contrast to a previously-encountered age-matched rat. After the test, rats were euthanized and brain tissue was then collected to quantify c-Fos labeling within the CA2 region. Compared to home cage controls and controls not exposed to the adult male, male and female rats exposed to the unrelated adult during preadolescence were unable to discriminate between a novel and previously encountered conspecific during the postadolescent test showing social memory deficits. The groups that showed social recognition deficits also had significantly fewer c-Fos-positive cells within the CA2 region compared to the control groups. These findings indicate that threatening psychogenic encounters during preadolescence can have detrimental long-term effects on social memory potentially via disrupted activity in the CA2 hippocampal region.